Research progress in the treatment of chronic fatigue syndrome through interventions targeting the hypothalamus-pituitary-adrenal axis - Zhang, Yi-Dan; Wang, Li-Na (Frontiers in Endocrinology, 2024)
Chronic fatigue syndrome (CFS) causes great harm to individuals and society. Elucidating the pathogenesis of CFS and developing safe and effective treatments are urgently needed. This paper reviews the functional changes in the hypothalamus-pituitary-adrenal (HPA) axis in patients with CFS and the associated neuroendocrine mechanisms. Despite some controversy, the current mainstream research evidence indicates that CFS patients have mild hypocortisolism, weakened daily variation in cortisol, a weakened response to the HPA axis, and an increase in negative feedback of the HPA axis. The relationship between dysfunction of the HPA axis and the typical symptoms of CFS are discussed, and the current treatment methods are reviewed.